A multi-proxy approach for reconstructing environmental dynamics since the mid Holocene in Lake Ismarida (Thrace, N. Greece) - Koukousioura, O.; Kouli, K.; Vouvalidis, K.; Aidona, E.; Karadimou, G.; Syrides, G. (Revue de micropaléontologie, 2020)
The paleoenvironmental evolution of Lake Ismarida in Thrace (Northern Greece) is revealed by the combined lithological, micropaleontological (benthic foraminifera, pollen and NPPS), molluscan analyses, magnetic susceptibility measurement and radiocarbon dating of a 5.8-m long sediment core. The mid Holocene evolution of the lake area is evidenced by the documentation of four sedimentary Units in the core ISMR-2, corresponding to four distinct evolutionary stages: (1) during ∼5500-3500 cal yr BP the lake area was a shallow marine environment characterized by an Ammonia beccarii, small rotaliids, miliolids, Bittium reticulatum and Veneridae spp. assemblage, marine dinoflagellate cysts, and low magnetic susceptibility values; (2) during ∼3500-3000 cal BP the environment is gradually tending to more isolated conditions forming an open lagoon, characterized by marine and euryhaline fauna and low magnetic susceptibility values; (3) during 3000 cal yr BP, the open lagoon presented a transition to an oligohaline inner lagoon, characterized by an Ammonia tepida, Haynesina germanica, Aubignyna perlucida, Pirenella conica, Cerastoderma glaucum and Abra spp. assemblage, sedges and aquatic vegetation. This restricted, entirely isolated from the sea inner lagoon could be definitely used as the landmark of the Lake Ismaris from Heorodotus, while describing the march of Xerxes through Thrace in 480 B.C.; (4) since ∼2000 cal yr BP to the present, the Lake Ismarida is formed, characterized by fresh-water indicators and aquatic pollen, Pseudoschizaea and high magnetic susceptibility values. Finally, the progradation of the Filiouris River deltaic deposits resulted to a 4 km wide deltaic plain between Lake Ismarida and the nowadays coastline. Pollen assemblages record the dominance of a rather rich deciduous forest in the area with traces of human presence in the lower part of the sequence, whereas the opening of the plant landscape under the increasing human pressure is evidenced after ∼ 3000 cal yr BP. Finally, an open vegetation pattern, contemporaneous with the retreat of forest vegetation, is evidenced in the area already before 2000 cal yr BP.